The Privy Council as the Final Court for the British Empire - Richardson, Ivor LM (Victoria University of Wellington Law Review, 2012)
After introductory comments on how the Judicial Committee functioned as the final court for the British Empire for over a century, this article discusses a range of highly unusual cases from India, Canada and New Zealand. The aim is to give something of the flavour of the Judicial Committee's work and its impact on local courts. The final section of the paper suggests conclusions that can be drawn from that survey.